Howard Baker : conciliator in an age of crisis - Annis, J. Lee (James Lee), 1957- (Lanham, Md. : Madison Books, 1995)
In the first biography of Baker ever written, J. Lee Annis examines Baker's life and his work as a conciliator and statesman who could make politics work. He argues that Baker brought to Washington diplomatic talents and a moderation that are lacking in politics today.
Includes bibliographical references (p. 253-263) and index.
Keywords: Baker, Howard H. -- 1925-; United States. -- Congress. -- Senate -- Biography; Statesmen -- United States -- Biography; Legislators -- United States -- Biography